Perception of the Indian Working Women considering Equity as an Investment Avenue: An Empirical Study - Hemavathy, P.; Gurusamy, Dr. S. (Ushus Journal of Business Management, 2015)
This long-lasting volatility in the stock market since the global financial crisis has been disappointing issue for the retail investors to invest in equity markets. Due to high volatility, new clients are scared to burn their fingers and existing investors are uncomfortable in roiling their portfolios.